2019
DOI: 10.17219/acem/99527
|View full text |Cite
|
Sign up to set email alerts
|

Association between expression of HOTAIR and invasiveness of gliomas, and its predictive value

Abstract: Association between expression of HOTAIR and invasiveness of gliomas, and its predictive value. AbstractBackground. Hox transcript antisense intergenic RNA (HOTAIR) is upregulated and associated with a poor prognosis in many cancer types. Besides, it is involved in the invasion and metastasis of non-small-cell lung cancer and nasopharyngeal carcinoma.Objectives. The aim of this study was to investigate the association between the expression of HOTAIR and the grades of gliomas, and to explore its possible mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…26 Likewise, a hox transcript antisense intergenic RNA (HOTAIR) was found with a higher abundancy in patients in Grades II-IV than those in Grade I. 27 Here, the GEO GSE2223 dataset suggested that GABPB1-AS1 was highly expressed in glioma tissues. This trend was validated in the clinical samples, and this lncRNA was analyzed to show an ideal prognostic value in glioma and indicate increased glioma grades.…”
Section: Discussionmentioning
confidence: 78%
“…26 Likewise, a hox transcript antisense intergenic RNA (HOTAIR) was found with a higher abundancy in patients in Grades II-IV than those in Grade I. 27 Here, the GEO GSE2223 dataset suggested that GABPB1-AS1 was highly expressed in glioma tissues. This trend was validated in the clinical samples, and this lncRNA was analyzed to show an ideal prognostic value in glioma and indicate increased glioma grades.…”
Section: Discussionmentioning
confidence: 78%
“…Collectively, these results suggest that HOTAIR may affect the potential of NSCLC cells to invade and migrate by altering the expression levels of MMPs and HOXA5 (72). In addition, Zhao et al (73) assessed 123 patients undergoing surgery for glioma and demonstrated that HOTAIR may facilitate invasion by increasing the expression levels of MMP-9, MMP-7 and VEGF. Kim et al reported that HOTAIR accelerates the invasiveness of cervical cancer cells by upregulating VEGF and MMP-9 expression (74).…”
Section: Vascular Endothelial Growth Factor (Vegf) Pathwaymentioning
confidence: 96%
“…Expression levels of HOTAIR > 0.40 had moderate predictive value for grades II-IV glioma. It promotes the invasion of gliomas through upregulation of the expression of matrix metalloproteinase-7 (MMP-7), matrix metalloproteinase-9 (MMP-9), and vascular endothelial growth factor (VEGF) [76]. Integrated in silico analysis, chromatin immunoprecipitation, and quantitative PCR data have shown that homeobox A9 (HOXA9) binds directly to the promoter of HOTAIR and might serve as a novel direct regulator of HOTAIR [77].…”
Section: Hotairmentioning
confidence: 99%